2019
DOI: 10.7759/cureus.5535
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Evisceration after Spontaneous Vaginal Cuff Rupture

Abstract: Small bowel evisceration after vaginal cuff rupture is a seldom seen surgical emergency. We report on a case of rupture seen in the emergency department in a patient eight weeks post hysterectomy. She presented to the emergency department by ambulance in the early morning hours with the complaint of acute severe abdominal pain along with nausea and vomiting. Diagnosis of this condition was confirmed after a thorough physical exam. Following manual reduction in the emergency department and immediate transfer fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Such a change may result in the vagina losing its valve-like structure. [ 14 ] In this case, a distended bladder was observed on the computed tomography. This could be a chronic complication of radical hysterectomy for cervical cancer and might have interfered with spontaneous reduction of the prolapsed bowel.…”
Section: Discussionmentioning
confidence: 79%
“…Such a change may result in the vagina losing its valve-like structure. [ 14 ] In this case, a distended bladder was observed on the computed tomography. This could be a chronic complication of radical hysterectomy for cervical cancer and might have interfered with spontaneous reduction of the prolapsed bowel.…”
Section: Discussionmentioning
confidence: 79%
“…This increased incidence could be explained by vaginal wall atrophy, which coincided with the triad of hypoestrogenism, chronic tissue devascularization, and pelvic floor weakness [ 10 , 15 ]. Most patients with transvaginal evisceration have previous gynaecological surgery or concomitant pelvic organ prolapse [ 10 , 15 , 16 ]. According to a review of all hysterectomies and pelvic repairs performed at Mayo Clinic from 1970 through 2001, Croak et al reported a 0.032% incidence of vaginal evisceration after a pelvic operation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other factors can influence this condition, such as lifestyle, hypothyroidism, obesity, multiparous women, previous pelvic radiotherapy, and poor collagen structure [ 1 10 ]. However, most case reports on the topic described a trigger moment for the evisceration as recent trauma or surgery, coughing, constipation or any other factor that would increase the intra-abdominal pressure suddenly in the context of pelvic floor weakness [ 8 , 16 , 18 , 19 ]. In premenopausal women, transvaginal intestinal evisceration is extremely rare and often associated with instrumentation, obstetric injury or coital trauma, which vaginal lacerations may accompany [ 7 , 10 , 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with our patient's presentation. Complications from transvaginal bowel herniation include bowel strangulation, bowel incarceration leading to ischemia, bowel perforation, intra-abdominal sepsis, peritonitis, septicemia, ileus, and deep vein thrombosis [ 1 , 2 , 5 ]. Diagnosis of evisceration is done by direct visualization during pelvic examination.…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal small bowel evisceration is a rare complication following a hysterectomy that is associated with advance age, enterocele, and previous vaginal surgery. “Rates are hard to determine due to the rarity, but literatures shows a rate between 0.032% and 1.25” [ 2 ]. The overall mortality rate is reported as 5.6 percent; however, when the bowel is strangulated through the vagina, the defect morbidity is higher [ 3 ].…”
Section: Introductionmentioning
confidence: 99%